An improved strong key exposure resilient auditing for cloud storage auditing - Ahila, R; Sivakumari, Dr. (International Journal of Engineering and Technology, 2018)
One of the most essential services of cloud computing is cloud storage. For cloud storage auditing, key exposure is a serious security problem which is solved by updating client secret keys regularly. However, this leads to local burdens to clients. A cloud source auditing with verifiable outsourcing of key updates paradigm was used to make the key updates as transparent for the client where Third Party Auditor (TPA) was played the role of authorized party. It holds only an encrypted version of clientâ€™s secret key. However, key exposure security problem is not fully solved by this scheme. So in this paper, improved strong key exposure resilient auditing is introduced to solve the key exposure security problem and improve the security of cloud storage. In the proposed paradigm, a novel key update technique is used where update message is created by TPA and it sends to the client. The client updates their signing secret key based on the update message and clientâ€™s private key. Moreover, public key is obtained from the client while updating a message which improves the security of cloud storage. Thus this scheme makes the malicious cloud unable to get the signing secret key in unexposed time periods.Â